Cognitive Behavioral Therapy for Insomnia Reduces Fear of Sleep in Individuals With Posttraumatic Stress Disorder - Kanady, Jennifer C. (J Clin Sleep Med, 2018)
STUDY OBJECTIVES: Our study aims were to examine (1) the association between fear of sleep and posttraumatic stress disorder (PTSD) symptoms, (2) the association between fear of sleep and subjective and objective insomnia symptoms and disruptive behaviors during sleep, and (3) whether fear of sleep decreases following cognitive behavioral therapy for insomnia (CBT-I). METHODS: Forty-five adults with PTSD and insomnia participated in the study. Fear of sleep was assessed using the Fear of Sleep Inventory; PTSD symptoms were assessed using the Clinician Administered PTSD Scale; and sleep disturbance symptoms were assessed using the Insomnia Severity Index, polysomnography, sleep diaries, and the Pittsburgh Sleep Quality Index Addendum for PTSD. Participants were randomly assigned to 8 weeks of CBT-I (n = 29) or a waitlist control condition (n = 16). RESULTS: Greater fear of sleep was associated with greater PTSD symptom severity, greater nightmare frequency, and greater hypervigilance intensity. Greater fear of sleep was associated with decreased wake after sleep onset (WASO), reduced total sleep time, and greater disruptive nocturnal behaviors. Following CBT-I, there was a significant reduction in fear of sleep compared to the waitlist condition. These improvements persisted 6 months later. CONCLUSIONS: Fear of sleep was related to sleep disturbances specific to trauma rather than “classic” insomnia symptoms. Unexpectedly, greater fear of sleep was associated with reduced WASO. These results may be related to having a truncated sleep period and thus more consolidated sleep. Fear of sleep deceased following CBT-I despite not being a permissible target for this research protocol and not being related to insomnia symptoms. CLINICAL TRIAL REGISTRATION: Registry: CinicalTrials.gov; Name: Treating People with Post-traumatic Stress Disorder with Cognitive Behavioral Therapy for Insomnia; Identifier: NCT00881647; URL: https://clinicaltrials.gov/ct2/show/NCT00881647 CITATION: Kanady JC, Talbot LS, Maguen S, Straus LD, Richards A, Ruoff L, Metzler TJ, Neylan TC. Cognitive behavioral therapy for insomnia reduces fear of sleep in individuals with posttraumatic stress disorder. J Clin Sleep Med. 2018;14(7):1193–1203.